2016
DOI: 10.1111/cas.12890
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic tumor burden predicts prognosis of ovarian cancer patients who receive platinum‐based adjuvant chemotherapy

Abstract: Volumetric parameters of positron emission tomography–computed tomography using 18F‐fludeoxyglucose (18F‐FDG PET/CT) that comprehensively reflect both metabolic activity and tumor burden are capable of predicting survival in several cancers. The aim of this study was to investigate the predictive performance of metabolic tumor burden measured by 18F‐FDG PET/CT in ovarian cancer patients who received platinum‐based adjuvant chemotherapy after cytoreductive surgery. Included in this study were 37 epithelial ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) is a molecular imaging technique, which can be used to evaluate tumor distribution and glucose metabolism in different kinds of cancers including gynecologic malignancy [10]. A few publications have explored the role of 18 F-FDG PET/CT quantitative parameters in epithelial ovarian cancer, usually lumping all histologic subtypes together [11][12][13][14][15][16][17][18][19][20]. PET/CT-based metabolic variables include maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV) and total lesion glycolysis (TLG).…”
Section: Introductionmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) is a molecular imaging technique, which can be used to evaluate tumor distribution and glucose metabolism in different kinds of cancers including gynecologic malignancy [10]. A few publications have explored the role of 18 F-FDG PET/CT quantitative parameters in epithelial ovarian cancer, usually lumping all histologic subtypes together [11][12][13][14][15][16][17][18][19][20]. PET/CT-based metabolic variables include maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV) and total lesion glycolysis (TLG).…”
Section: Introductionmentioning
confidence: 99%
“…One technique in clinical practice that takes advantage of glycolysis is the FDG-PET/CT (2,3). Glucose is transported into the cytoplasm via GLUTs, especially GLUT1.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells are thought to exclusively activate glycolysis, even in the presence of adequate oxygen. One technique in clinical practice that takes advantage of glycolysis is fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) (2,3). Normally, in cancer cells, glucose is transported into the cytoplasm via glucose transporters (GLUTs), especially GLUT1 (4).…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer, a positive PET scan was associated with poor overall survival, but semiquantitative data were not proven to be an effective tool to predict disease progression . Yamamoto et al reported that metabolic tumor volume and total lesion glycolysis could predict the prognosis of ovarian cancer patients who underwent primary surgery followed by platinum‐based chemotherapy . As described above, the pretreatment assessment of the SUVmax could be useful for predicting the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%